Multidisciplinary Investigation of the Transform Fault Zones Doldrums and Vema during Cruise 45 of the R/V “Akademik Nikolaj Strakhov” - Ivanova E. V.; Skolotnev S. G.; Borisov D. G.; Demidov A. N.; Bich A. S.; Gippius F. N.; Gryaznova A. S.; Dobroliubova K. O.; Zinger T. F.; Korshunov D. M.; Levchenko O. V.; Mashura V. V.; et al. (Oceanology, 2020)
Abstract: Herein we provide information on the integrated geological, geophysical, sedimentological, paleoceanographic, hydrophysical and biological investigations in the Central Atlantic during the cruise 45 of the R/V “Akademik Nikolaj Strakhov” in October-November 2019. The preliminary scientific results are discussed.